Effect of Process Parameters on Pectin Extraction from Dragon Fruit (Hylocereus polyrhizus) Peels via Chemical and Physical Treatment - Rubaiyi, M. Zaid; Zularisam, A. W.; Mimi Sakinah, A. M. (AENSI Publishing, 2016)
Dragon fruit (Hylocereus polyrhizus) peel was found to be one of the potential sources of pectin. The combination of physical and chemical treatments namely mild ultrasound, stirring and citric acid has been applied with the aim to get the high yield of pectin during extraction. The influence of several process namely agitation, temperature, time, pH and liquid solid ratio during extraction process were investigated. The one factor at a time (OFAT) method was used to determine the possible best levels of each factor during extraction. The pectin obtained from these experiments was compared in term of yield based on dry weight. The highest yield of pectin 42.5% (w/w) was obtained when the extraction was carried out at agitation, temperature, time, pH and solid liquid ratio of 250 rpm 70oC, 120 min, pH of 1.5 and 1:10 (w/v), respectively.